A Comparison of Two Cognitive Pretesting Techniques Supported by Eye Tracking. (October 2016) - Neuert, Cornelia E.; Lenzner, Timo
In questionnaire pretesting, supplementing cognitive interviewing with eye tracking is a promising new method that provides additional insights into respondents' cognitive processes while answering survey questions. When incorporating eye tracking into cognitive interviewing, two retrospective probing techniques seem to be particularly useful. In the first technique—retrospective probing—participants complete an online questionnaire, while cognitive interviewers monitor participants' eye movements in an adjacent room and note down any peculiarities in their reading patterns. Afterward, the interviewers ask targeted probing questions about these peculiarities in a subsequent cognitive interview. In the second technique—gaze video cued retrospective probing—respondents are additionally shown a video of their eye movements during the cognitive interview. This video stimulus is supposed to serve as a visual cue that may better enable respondents to remember their thoughts while answering the questions. We examine whether one of the two techniques is more effective when it comes to identifying problematic survey questions. In a lab experiment, participants' eye movements ( n = 42) were tracked while they completed six questions of an online questionnaire. Simultaneously, their reading patterns were monitored by an interviewer for evidence of response problems. After completion of the online survey, a cognitive interview was conducted. In the retrospective probing condition, probing questions were asked if peculiar reading patterns were observed during the eye-tracking session (e.g., rereadings of specific words or text passages). In the other condition, participants were shown a video of their recorded eye movements, in addition to receiving probing questions about the questions displayed. Results show that both techniques did not differ in terms of the total number of problems identified. However, gaze video cued retrospective probing identified fewer unique problems and fewer types of problems than pure retrospective probing.